Factors influencing consumers motivations for healthy eating and food-mood relation of people's with and without depressive disorder - Bartkiene, Elena (2019)
The aim of this study was to evaluate relation between the consumers gender, age, education, civil state, profession and its field with their perception, emotional motivations and selection of information sources about a healthy eating. In addition, to evaluate possible relation of the food choice and people‘s mood, the initial study about the emotions induced by the different tastes of food for people's with and without depressive disorder was performed. It was established that the gender is significant factor on the most of the emotional motivations. Also, participants age have a significant influence on motivation “food makes me feel good“, as well as education have a significant influence on perceptions about a healthy eating. Most of the analysed perceptions were significantly influenced by civil state, profession and professional field of the participants. The results obtained by using FaceReader technic showed higher sensibility, than the evaluation by using hedonic scale, which can be influenced by participants previous emotions, which were induced by memory about food uses in the past, and it was established that the mood has a link with the choice of food. Finally, FaceReader is very promising technique to detect differences in facial emotion expressions induced by different taste of food for different mood people's groups, but more research is needed to see how this technology performs in more complex testing procedures, simulated or ‘‘real life’’ environments.